Priorities for irrigation investment in Malawi - Chafuwa, Chiyembekezo (International Food Policy Research Institute, 2017)
This policy note explores priorities for investment in irriga-tion in Malawi, and examines the trade-offs between invest-ment in new irrigation infrastructure, versus rehabilitation and maintenance of existing irrigation infrastructure. By reviewing empirical studies and government publications, the note exam-ines investment trends in the irrigation sector, and further identifies possible channels through which maximum benefits can be accrued from irrigation in Malawi.